Alternative surface reaction route in the atomic layer deposition of NbN thin films for reduced resistivity - Lee, Hyeok Jae; Jang, Seo Young; Lee, Hye Min; Sung, Ju Young; Kim, Se Eun; Jeon, Jae Deock; Yun, Yewon; Lee, Sang Woon (Journal of Alloys and Compounds, 2023)
Transition metal nitride thin films such as TiN are necessary as conducting electrodes in memory and transistor devices. Due to their high work function (> 4.7 eV), NbN thin films have recently attracted attention to replace TiN thin films as capacitor electrodes using atomic layer deposition (ALD) process in dynamic random access memories (DRAMs) to reduce leakage currents in the capacitors. Unfortunately, the NbN ALD process using NbCl5 and NH3 as the Nb precursor and nitrogen source resulted in a high resistivity (> 500 μΩ·cm) despite its low bulk resistivity (∼10 μΩ·cm at 300 K) because of the residual Cl impurity (> 5%) within the NbN film. In this study, an alternative ALD surface reaction pathway is proposed by introducing H2S gas pulses between the NbCl5 and NH3 pulse steps to lower the Cl impurity concentration. Using the alternative ALD reaction, the residual Cl concentration was reduced below 1.5% (decrease by > 50%) at the specific ALD deposition temperature of 673 K. Finally, this reaction produced a greater decrease in the resistivity (> 30%) of NbN thin films than the conventional NbN ALD at 673 K.
Keywords: Atomic-layer deposition; Conducting electrodes; Deposition process; High work function; Metal thin film; NbN thin film; Nitride thin films; Reaction routes; Reduced resistivity; Transition metal nitrides; Atomic layer deposition; Metal thin film; NbN; Surface reaction